Role of microvascular pericyte dysfunction in antibody-mediated rejection following kidney transplantation - Jie Xu; Junyan Pu; Hao Chen; Li Sun; Shuang Fei; Zhijian Han; Jun Tao; Xiaobing Ju; Zijie Wang; Ruoyun Tan; Min Gu (Renal Failure)
Objective To investigate the role of microvascular pericyte dysfunction in antibody-mediated rejection (ABMR) of transplanted kidneys.Methods A total of 160 patients who underwent kidney transplantation in our hospital from 2004 to 2020 were enrolled, divided into 4 groups: ABMR group (n = 79), TCMR group (n = 20), mixed rejection group (n = 25) and control group (n = 36). Postoperative renal function indicators were compared, and immunohistochemical and immunofluorescence staining was performed on graft tissues and mice models using the pericyte marker PDGFR-β. An in vitro pericyte dysfunction model was co-cultured with vascular endothelial cells for functional assessment through Western blotting, PCR, and wound healing tests. KEGG pathway analysis from the GEO database identified gene expression changes in pericytes, which were further analyzed using electron microscopy and Western blot techniques.Results There were statistically significant differences in creatinine, urea nitrogen, urine protein, and eGFR among the groups over time, with ABMR displaying the poorest outcomes. Immunohistochemistry revealed lower pericyte expression in ABMR, which was confirmed in mouse model studies showing reduced PDGFR-β expression in ABMR. KEGG analysis highlighted decreased autophagy in pericyte dysfunction, supported by electron microscopy and Western blot findings indicating reduced autophagy and pericyte damage, which could be reversed by chloroquine.Conclusion ABMR episodes worsened the long-term prognosis of transplanted kidneys. pericyte dysfunction appears to be one of the crucial causes of poor prognosis in ABMR patients. In vitro studies demonstrated that dysfunction of microvascular pericytes can result in damage to vascular endothelial cells, with autophagy impairment being a significant mechanism contributing to pericyte dysfunction.